Penerapan Model Problem Based Learning Meningkatkan Hasil Belajar Matematika Materi Keliling Bangun Datar Peserta Didik Kelas III SDN 13 Mataram - Indriani, Ni Made Puja Swari; Dahlia, Kurnia Ariani; Rohyani, Helmi; Arjudin, Arjudin (Journal of Science Instruction and Technology, 2023)
This study is set back by the lack of training for learners in identifying and solving a mathematical problem it is intended to describe and expansion- based problem model. The kind of research of classroom action (PTK) employs qualitative and quantitative approaches. The design of research involves planning, the performance of observation and reflection. The research subject was the teacher and student of the fourth grade the fields of 21 persons of 12 women and 9 boys. The data collection is through observation, testing and RPP assessment. Research shows: a) average RPP cycles I 76.78% increased in cycle II to be 96.42%.) b) implementation on the aspect of the teacher cycle I 76.78% increased on cycle II 92.85 %6): c) implementation on learning cycle I 75% increased on cycle II 92.85%): d) average value of studying cycle I 67.38% increased to 85.85% on sıklus II and thus the based problem model ıng could increase learners' learning on the circumference SDN 13 Mataram.